Incidence of and mortality from cancer in hypertensive patients. Issue 6878 (6th March 1993) - Hole, D J; Hawthorne, V M; Isles, C G; McGhee, S M; Robertson, J W; Gillis, C R; Wapshaw, J A; Lever, A F
Abstract : OBJECTIVES--To assess incidence of and mortality from cancer in hypertensive patients taking atenolol, comparing the findings with two control populations and with hypertensive patients taking other drugs. DESIGN--Retrospective analysis of patients first seen in the Glasgow Blood Pressure Clinic between 1972 and 1990. Patients' records were linked with the registrar general's data for information on mortality and with the West of Scotland Cancer Registry for information on incident and fatal cancers. Cancers were compared in patients and controls and in patients taking atenolol, beta blockers other than atenolol, and hypotensive drugs other than beta blockers. SUBJECTS--6528 male and female patients providing 54, 355 years of follow up. SETTING--Hypertension clinic in Glasgow. MAIN OUTCOME MEASURES--Observed numbers of cancers in clinic patients were compared with expected numbers derived from cancer rates in two control populations adjusted for age, sex, and time period of data collection. RESULTS--Cancer mortality was not significantly different in clinic patients as a whole and controls. Incident and fatal cancers were not significantly increased in male or female patients taking atenolol. Cancer incidence did not rise in the clinic after a large increase in prescriptions for atenolol after 1976. CONCLUSION--This analysis does not suggest a link between atenolol and cancer.